2008
DOI: 10.1088/1742-6596/96/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of an air-jet spinning nozzle with a slotting-tube

Abstract: Abstract. Slotting-tube is a critical component of a nozzle of an air-jet spinning machine. It affects flow characteristics in the nozzle, and the fibres motion and yarn properties as well. A realizable k-ε turbulence model is adopted to simulate the airflow field inside the nozzle with the slotting-tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The extensive use of the model has highlighted both its robustness and low computational expense Haque et al [18]. Standard k-ε turbulent models were also widely used for the numerical analyses of the nozzle in which pressurized air is fed Patnaik et al [6]; Guo & Yu [19]; Guo & Yu [9]; Rengasamy et al [8]. Although k-ε turbulent model produces the reasonable results, the model does not perform very well for the flows at the boundary layer separation, sudden changes in swirling and rotating flows and flows over the curved surfaces Guo et al [9][10][11].…”
Section: Solution Algorithm: Turbulence Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The extensive use of the model has highlighted both its robustness and low computational expense Haque et al [18]. Standard k-ε turbulent models were also widely used for the numerical analyses of the nozzle in which pressurized air is fed Patnaik et al [6]; Guo & Yu [19]; Guo & Yu [9]; Rengasamy et al [8]. Although k-ε turbulent model produces the reasonable results, the model does not perform very well for the flows at the boundary layer separation, sudden changes in swirling and rotating flows and flows over the curved surfaces Guo et al [9][10][11].…”
Section: Solution Algorithm: Turbulence Modelsmentioning
confidence: 99%
“…Standard k-ε turbulent models were also widely used for the numerical analyses of the nozzle in which pressurized air is fed Patnaik et al [6]; Guo & Yu [19]; Guo & Yu [9]; Rengasamy et al [8]. Although k-ε turbulent model produces the reasonable results, the model does not perform very well for the flows at the boundary layer separation, sudden changes in swirling and rotating flows and flows over the curved surfaces Guo et al [9][10][11]. Wilcox [20] suggested another model (k-ω) based on the [20]activated in the near-wall region and the standard k-ε model activated in the outer wake region and in free shear layers Dhinsa et al [17]; Bartosiewicz et al [21]; Haque et al [18].…”
Section: Solution Algorithm: Turbulence Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little work has been reported regarding the flow field in this geometry. Our earlier reports [28,29] studied the fluid behavior inside this geometry and discussed the function of the slotted-tube and the effect of injector pressure using a numerical method. Spinning test studies have shown that yarn properties are strongly dependent on the groove parameters of the slotted-tube [30].…”
Section: Introductionmentioning
confidence: 99%